2008
DOI: 10.1186/1475-2867-8-12
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 overexpression proves to be independent marker for breast cancer progression

Abstract: Background: Breast cancer is the most common cancer and cause of deaths in women around the world. Oncogene amplification usually occurs late in tumor progression and correlates well with aggressiveness of tumor. In fact the function of the S100A4 protein and its role in metastasis is unclear at present. The purpose of the study was to determine the expression of S100A4 protein in the invasion status and metastatic potential of breast cancer by using tissue microarray and to determine its role in breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 41 publications
5
33
0
2
Order By: Relevance
“…We speculate that by binding to TG2, S100A4 could potentiate integrin-mediated signaling, and thus enhance cell adhesion and migration, leading to increased metastasis in tumors in which both proteins are overexpressed and released to the ECM. Indeed, both TG2 and S100A4 were found to contribute to the high metastatic properties of several cancers, such as breast and colorectal tumors [42][43][44][45]. It cannot be ruled out that TG2 and S100A4 also interact inside tumor cells (as they both have important intracellular functions) or other cell types as well, and either by cross-linking activity of TG2 or additional protein-protein interactions contribute to the pathomechanism of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that by binding to TG2, S100A4 could potentiate integrin-mediated signaling, and thus enhance cell adhesion and migration, leading to increased metastasis in tumors in which both proteins are overexpressed and released to the ECM. Indeed, both TG2 and S100A4 were found to contribute to the high metastatic properties of several cancers, such as breast and colorectal tumors [42][43][44][45]. It cannot be ruled out that TG2 and S100A4 also interact inside tumor cells (as they both have important intracellular functions) or other cell types as well, and either by cross-linking activity of TG2 or additional protein-protein interactions contribute to the pathomechanism of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…S100A4 belongs to the S100 calcium binding protein family and may be characterized as a cytoplasmic protein that promotes cellular motility via direct interaction with myosin-IIA and also has functions in cell cycle progression. Its overexpression has been documented in breast (9)(10)(11)(12), gastric (13), colorectal (14)(15)(16), esophageal squamous cell (17) and gallbladder carcinoma (18), ovarian (19) and bladder cancer (20), papillary thyroid carcinoma (21,22) and non-small cell lung cancer (23). In addition, its upregulation has been associated with disease progression, metastasis and decreased patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, S100A4 was one of only 25 genes found upregulated in three different mammary cancer stem cell expression signatures (Gupta et al, 2009). Numerous other reports on clinical material from breast (Ismail et al, 2008;Lee et al, 2004), bladder (Matsumoto et al, 2007), colorectal (Flatmark et al, 2003;Gongoll et al, 2002), melanoma and several other types of cancer (Garrett et al, 2006) have confirmed the association between S100A4 expression, and a more severe prognosis. Collectively these findings suggest S100A4 as a major determinant of breast cancer progression.…”
mentioning
confidence: 56%
“…The link between expression of S100A4 in breast carcinoma cells, and poor patient outcome, has been soundly established (Ismail et al, 2008;Lee et al, 2004;Rudland et al, 2000). Since very few studies have looked at the expression and function of this protein in nonmalignant cells and tissue, the aim for the present work was to elucidate the biological function of S100A4 in normal mammary gland.…”
Section: Discussionmentioning
confidence: 99%